Hybridoma-free generation of monoclonal antibodies - Pasqualini, Renata (Proc Natl Acad Sci U S A, 2003)
Production of monoclonal antibodies requires immortalization of splenocytes by somatic fusion to a myeloma cell line partner (hybridomas). Although hybridomas can be immortal, they may depend on a feeder cell layer and may be genetically unstable. Since the inception of hybridoma technology, efforts to improve efficiency and stability of monoclonal antibody-producing cell lines have not brought about substantial progress. Moreover, suitable human multiple myeloma-derived cell lines for the production of human antibodies have been very difficult to develop. Here we report a strategy that greatly simplifies the generation of antibodies and eliminates the need for hybridomas. We show that splenocytes derived from transgenic mice harboring a mutant temperature-sensitive simian virus 40 large tumor antigen under the control of a mouse major histocompatibility promoter are conditionally immortal at permissive temperatures and produce monoclonal antibodies. This simple approach may become a method of choice for generation and production of both polyclonal and monoclonal antibodies with advantages in high-throughput discovery and antibody-based immunotherapy.